The impact of Working Capital, Product Innovation, Marketing Strategies, and Business Location on the Success of Microentreprises in the Culinary Sector in Bima City - Amanda Soviana; Khas Sukma Mulya; Muhammad Rizkan (JURNAL ECONOMINA, 2026)
his study aims to analyze the effects of business capital, product innovation, marketing strategies, and business location on the success of micro culinary businesses in Bima City. The study employed a quantitative approach using field research on 100 business owners selected through purposive sampling and the Slovin formula, and the data were analyzed using multiple linear regression. The results show that business capital and business location have a positive and significant partial effect, while product innovation and marketing strategy do not have a significant effect. Simultaneously, all four variables have a positive and significant effect, with an adjusted R-squared of 0.469. These findings confirm that sufficient capital and an appropriate location are the primary determinants of the success of micro culinary businesses in Bima City.